2017
DOI: 10.4269/ajtmh.16-0718
|View full text |Cite
|
Sign up to set email alerts
|

Noma: Overview of a Neglected Disease and Human Rights Violation

Abstract: Noma is an orofacial gangrene affecting malnourished children and mainly observed in tropical countries, particularly sub-Saharan Africa. Epidemiological data on noma are scarce, but a current estimate of the global incidence is 30,000-40,000 cases per year, with a mortality rate of approximately 85% and a burden of disease calculated to be a loss of 1-10 million disability-adjusted life years. The etiology of noma is multifactorial with malnutrition as an ever present factor, often in combination with concomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 36 publications
1
94
0
Order By: Relevance
“…The risk of noma disease mostly occurs in children aged between 2-6 years with a weak immune system, extreme poverty, poor oral hygiene, malnutrition, malaria, kwashiorkor (edema), measles, HIV/AIDS infection, and adult adolescents with weak immune system (Jain & Ranka, 2017;Neville, Damm, Allen, & Chi, 2019;Prado-calleros et al, 2017;Srour, Marck, & Baratti-mayer, 2017;WHO, 2016). The results of research conducted on 159 cases of acute cancrum oris (noma) treated at Sokoto Hospital, Nigeria, showed that 42.20% of noma patients were accompanied by measles and 42.10% were accompanied by malnutrition.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The risk of noma disease mostly occurs in children aged between 2-6 years with a weak immune system, extreme poverty, poor oral hygiene, malnutrition, malaria, kwashiorkor (edema), measles, HIV/AIDS infection, and adult adolescents with weak immune system (Jain & Ranka, 2017;Neville, Damm, Allen, & Chi, 2019;Prado-calleros et al, 2017;Srour, Marck, & Baratti-mayer, 2017;WHO, 2016). The results of research conducted on 159 cases of acute cancrum oris (noma) treated at Sokoto Hospital, Nigeria, showed that 42.20% of noma patients were accompanied by measles and 42.10% were accompanied by malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…This lesion can function as a place for the entry of microorganisms that are responsible for the disease process (Jain & Ranka, 2017). Noma is usually preceded by diseases that can decrease the immune system, such as measles, malaria, diarrhea, tuberculosis, or inflammation of the necrotizing ulcerative gums which are considered as risk factors or significant precursors to noma events (Jain & Ranka, 2017;Srour, Marck, & Baratti-mayer., 2017;WHO, 2016). Noma occurs mainly in poor communities who are untouched by health services and have a nomadic lifestyle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations